Applying Cognitive Processing Therapy to Posttraumatic Stress Disorders Syndrome among Internally Displaced Youth Victims of Terrorism in Nigeria (Global Journal of Human-Social Science, 2018)
The main concern of this research was to identify those who were experiencing Posttraumatic Stress Disorder Syndrome after Boko Haran terror attacks and to employ Cognitive Processing Therapy strategy in minimising or preventing probable long-term psychological distress. Four (4) practicing counselling psychologists were involved. Traumatic Screening Questionnaire (TSQ) and Checklist-Civilian Version (PCT-C) were pilot-tested and used for the research. Descriptive survey design was used. Purposive and Stratified random samplings were used to select the youths. Cognitive Process Therapy treatment model -Civilian Version (PCL-C) was applied. Total sample population was 76. Findings showed that, after undergone Cognitive Processing Therapy, a total population of 57 (75%) of the respondents experienced little to no severity PTSD while 19 (25%) of respondents experienced moderate to moderately of PTSD.
Keywords: posttraumatic stress disorders syndrome; internally displaced youth victims of boko haran terrorism; cognitive processing therapy